Arroz deu cacho e o feijão floriô: Repertórios dos movimentos sociais do campo na ocupação da Fazenda Cipó Cortado - FONSECA, Verônica Viana da (2023)
The rural social movements present themselves as protagonists in the struggle for land and citizenship in the Região Tocantina. The case of the occupation of the Cipó Cortado Farm is emblematic, a land conflict that lasted for decades, gaining national and even international repercussions. This research, which has the title: “Anos de Luta, Dias de Glória – Repertórios dos Movimentos Sociais do Campo na Ocupação da Fazenda Cipó Cortado”, uses the theory of the political process, developed by Charles Tilly, Sidney Tarrow, and its reverberations in Brazil in the studies of Angela Alonso and Breno Bringel, seeking to reveal the categories, repertoires, tactics, performances and symbolic representations of the rural social movements, namely the Sindicato de Trabalhadores e Trabalhadoras Rurais de João Lisboa - MA and the Movimento dos Trabalhadores e Trabalhadoras Rurais Sem-Terra, in the process of occupation and conquest of those lands. It is a multidisciplinary socio-historical analysis, an overlap between sociology and history, with elements from anthropology and geography. A qualitative methodology was used, anchored in the related bibliography, in the collection of data in archives and field research using Oral History, focused on the trajectories of those subjects, rescued through participant observation, with rounds of conversations and interviews, their life stories, memories, speeches, habits, practices, seeking to reconstitute the mosaic of the struggle for the lands of Cipó Cortado.